2013
DOI: 10.1111/dme.12247
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia, fear of hypoglycaemia and quality of life in children with Type 1 diabetes and their parents

Abstract: Fear of hypoglycaemia and not episodes of hypoglycaemia per se is associated with increased psychological burden for children with Type 1 diabetes. Interventions to reduce fear of hypoglycaemia in these families may improve their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
158
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(176 citation statements)
references
References 36 publications
(50 reference statements)
11
158
2
4
Order By: Relevance
“…None of the children in this group implied that they had worries or concerns about future hypoglycaemic episodes. This finding differs to questionnaire research which implied that children aged 8 -18 years with T1DM fear hypoglycaemia [12], however this may reflect an older sample and/or larger age range than that used in our study. It also differs from the parents' perspective, which suggested that parents of children with T1DM worry about exercise-induced hypoglycaemic episodes, especially during the night after active days [9].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…None of the children in this group implied that they had worries or concerns about future hypoglycaemic episodes. This finding differs to questionnaire research which implied that children aged 8 -18 years with T1DM fear hypoglycaemia [12], however this may reflect an older sample and/or larger age range than that used in our study. It also differs from the parents' perspective, which suggested that parents of children with T1DM worry about exercise-induced hypoglycaemic episodes, especially during the night after active days [9].…”
Section: Discussioncontrasting
confidence: 99%
“…Symptoms range from shaking and sweating (mild hypoglycaemia) to coma (severe hypoglycaemia) [11]. A questionnaire study identified fear of hypoglycaemia in children aged 8 -18 years with T1DM [12]. Questionnaire methods enable a large sample size, but limit the depth of response a child can…”
Section: Introductionmentioning
confidence: 99%
“…Hypoglycaemia is one of the main limiting factors to obtaining optimal metabolic control. In addition, fear of hypoglycaemia can significantly impair the quality of life of the child and its parents [25]. Previous studies have shown a significant improvement in quality of life upon starting insulin pump therapy, in particular with respect to worrying about hypoglycaemia [26].…”
Section: Discussionmentioning
confidence: 99%
“…23 Additional research strengthens this hypothesis and shows that African American children in particular suffer from poorer metabolic control due to lower family income that precludes the purchase of proper health insurance and care. 24 Despite the strong evidence of negative correlations between SES and metabolic balance, Kichler et al 25 surprisingly argue in their research that in a study of Hispanic youth with T1DM, those having a more recent generational status (ie, their parents had immigrated more recently) in the US exhibited better adherence. The authors hypothesized that those who are less acculturated may have greater respect for medical staff, which may be associated with better adherence.…”
Section: Ses and Ethnic Backgroundmentioning
confidence: 97%